A New Method for MPPT Algorithm Implementation and Testing, Suitable for Photovoltaic Cells - SFIRAT, A.; GONTEAN, A.; BULARKA, S. (Advances in Electrical and Computer Engineering, 2018)
The goal of this paper is to present an implementation method for a Maximum Power Point Tracking (MPPT) algorithm using an electronic load and custom designed LabView software. The aim is to facilitate the testing of the algorithm in laboratory conditions, before it can be used in the real world, improving development time, facilitating cost reduction and offering confidence in the design. This paper analyses the most suitable MPPT algorithms for testing purposes and suggests a complete software and hardware implementation for hardware in the loop testing which can facilitate in-depth evaluation of different algorithms. In order to replicate realistic stimuli for the MPPT algorithm, a solar array simulator has been designed. Using the proposed method, the performance of various MPPT algorithms for different atmospheric conditions can be evaluated. The hardware and software setup have been tested and validated in laboratory conditions. The experimental results have validated the proposed evaluation method and the good dynamic response of the MPPT algorithm. Index Terms--algorithms, maximum power point trackers, photovoltaic cells, simulation, solar energy.